Power increases the self‐serving bias in the attribution of collective successes and failures. (5th December 2018) - Lammers, Joris; Burgmer, Pascal
Abstract: Three studies test the effect of power on the self‐serving bias in attributing collective outcomes. The first two studies measure (Experiment 1) and manipulate (Experiment 2) power and then measure the internal (vs. external) attribution of past successes and failures. Consistently, those who feel powerful show a stronger self‐serving tendency to selectively attribute successes internally and failures externally than those who feel powerless. Experiment 3 compares the effects of power (control over others) and personal control (over oneself). We find that power increases the self‐serving bias, but a lack of control can limit this effect by reducing the external attribution of failures. Presumably, people who lack control are disinclined to attribute outcomes—including failures—externally because doing so would further aggravate their lack of control. Together, these results suggest that power increases a bias in the attribution of success and failure and thus presents a fundamental challenge to good leadership.